2009
DOI: 10.7326/0003-4819-151-5-200909010-00004
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a Mediterranean-Style Diet on the Need for Antihyperglycemic Drug Therapy in Patients With Newly Diagnosed Type 2 Diabetes

Abstract: Second University of Naples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
163
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(180 citation statements)
references
References 31 publications
6
163
1
1
Order By: Relevance
“…In our study, however, the mean decline in HbA1c was substantially greater, falling by 2.5 ± 2.1%. Similarly, in our study, total cholesterol and triglycerides decreased by 0.79 ± 1.01 mmol/l and 0.56 ± 0.67 mmol/l, respectively, which exceeded values reported in other studies 7, 8. However, the modest improvements we observed in blood pressure were in line with previous reports 7, 8…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, however, the mean decline in HbA1c was substantially greater, falling by 2.5 ± 2.1%. Similarly, in our study, total cholesterol and triglycerides decreased by 0.79 ± 1.01 mmol/l and 0.56 ± 0.67 mmol/l, respectively, which exceeded values reported in other studies 7, 8. However, the modest improvements we observed in blood pressure were in line with previous reports 7, 8…”
Section: Discussionsupporting
confidence: 90%
“…In the LookAHEAD study and a Mediterranean diet trial in persons with type 2 diabetes, HbA1c decreased by 0.6% and 1.2%, respectively, after 1 year 7, 8. In our study, however, the mean decline in HbA1c was substantially greater, falling by 2.5 ± 2.1%.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Moreover, a recent small crossover trial showed that a MeDiet reduced the average levels of Hb1Ac [22]. In addition, in an experimental design, the MeDiet achieved a better glycaemic control than a low-fat diet [23]. An inverse association between adherence to the MeDiet and fasting plasma glucose, insulin and the homeostasis model assessment index of insulin resistance (HOMA-IR) levels has also been found in non-diabetic participants and has thus been interpreted as a protective effect of the MeDiet against T2DM [24].…”
Section: Discussionmentioning
confidence: 99%
“…Where SD was not available, the authors of the original publication have been asked for the missing data. With regard to one trial [18], the baseline SD had to be imputed. We assumed that this is a valid procedure, since the baseline and post-intervention SD were found to be similar within the other trials included in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%